Hidup Peribadatan: Perayaan Ekaristi Secara Online dan Offline selama Masa Pandemi COVID-19 - Vries, Richardo Martin Emmanuel De; Wiguna, Vincentius Agsuko (Felicitas, 2021)
The Eucharist is the source and pinnacle of Christian life. Faithfully, the people follow the Eucharistic Celebration in their churches. The faithful are there to receive the Word of God and eat the Body of Christ. However, the Covid-19 pandemic changed everything. Eucharistic celebrations are held online or offline according to circumstances. To find out the state of the people's faith, in religious life, this paper intends to present the results of research conducted in five parishes in the city of Surabaya during the pandemic. From here, the response of the people can be seen when participating in the Eucharistic Celebration both online and offline.